764. Will the Addition of Probiotics to Patients Receiving Intravenous Antimicrobial Therapy Reduce the Incidence of Healthcare Facility-Onset Clostridium difficile Infection?. (4th December 2021) - Shah, Punit; Kay, Jessica; Akogun, Adanma; Wise, Silvia; Aly, Sarfraz; Daoura, Nicolas
Abstract: Background: Exposure to antimicrobials is a known risk factor for Clostridium difficile infection (CDI). Antimicrobials cause collateral damage by disrupting the natural intestinal microbiota allowing for C.difficile to thrive and production of C.difficile toxins. Probiotics could modulate the onset and course of CDI. However, the data on probiotics for the prevention of CDI is conflicting. Methods: We conducted an IRB approved retrospective cohort study at a 340-bed community hospital. All hospitalized patients from August 1, 2017 through July 31, 2020 were evaluated for enrollment. Patients were included if they received at least one dose of intravenous (IV) antibiotic and had a length of stay of at least 3 days. Patients were excluded if they were younger than 18 years, or if they had a positive C.difficile polymerase chain reaction test before antibiotics were started. The primary outcome was the incidence of healthcare facility-onset Clostridium difficile infection (HO-CDI). Descriptive statistics were used to analyze demographics data, and the primary outcome of HO-CDI was analyzed using Fisher's exact test and multiple logistic regression. Results: A total of 20, 257 patients received IV antibiotics during the study time frame. Of these, 2, 659 patients received probiotics. Primary outcome of HO-CDI occurred in 46 patients in the IV antibiotics alone cohort (0.26%) and 5 patients in the probiotics plus IV antibiotics cohort (0.19%). The difference in HO-CDI between these two groups was not statistically significant, p=0.677. A multiple logistic regression was performed to see the impact of proton pump inhibitor use, age, ICU admission, Charlson Comorbidity Index, probiotic use and CDI in the past 12 months on the primary outcome. C.difficile infection in prior 12 months [OR 3.37, 95%CI 1.04-10.97] and ICU admission [OR 1.81, 95%CI 1.02-3.19] were associated with higher CDI. The addition of probiotics to patients on IV antibiotics did not exhibit a protective effect [OR 0.72, 95% CI 0.28-1.81]. Conclusion: The addition of probiotics to standard of care was not beneficial in the prevention of HO-CDI. We endorse robust antibiotic stewardship practices as part of the standard of care bundle that institutions should employ to decrease the incidence of HO-CDI. Disclosures: All Authors : No reported disclosures